Influence of the cattle body weight estimation for drug dosing on the pharmacokinetic and efficacy of ivermectin against Rhipicephalus (Boophilus) microplus - Miró, Maria Victoria; Sarli, Macarena; Rossner, Maria Victoria; Gomez, Viviana Daniela; Toffaletti, Jose Rodolfo; Lifschitz, Adrian Luis; Nava, Santiago (Systematic and Applied Acarology Society, 2022)
This study aimed to evaluate how the method of body weight estimation of a herd (average vs individual) for drug dosing may affect the pharmacokinetics and therapeutic efficacy of ivermectin 3.15% against Rhipicephalus (Boophilus) microplus. The trial was performed in two populations of R. (B.) microplus with different levels of susceptibility to ivermectin: San Martín (SM) (incipient resistance) and Colonia Benítez (CB) (susceptible). Twenty-one (SM) and forty-two (CB) 12-month-old Braford heifers, naturally infested with R. (B.) microplus, were individually weighed and divided into three groups (G). G1 and G2 were treated with a dose of ivermectin 3.15% (IVOMEC GOLD®) at a dose rate of 630 μg/kg of body weight (1 mL/50 kg). G1 received a uniform dose of ivermectin calculated according to the average of the individual body weights. G2 received a dose of ivermectin calculated according to the exact body weight of each animal. G3 were the control group. Ivermectin concentrations were measured from blood samples from day 1 to day 21 post-treatment. The efficacy of the treatment was evaluated by counting female ticks. In both populations the differences in the doses of ivermectin administered did not affect the pharmacokinetics and therapeutic efficacy of the drug. Nevertheless, it is necessary to avoid the sub-dosage of cattle to reduce the selection pressure for resistance on the tick populations.